Grid‐supportive electric vehicle charging methodology with energy management for coordinated frequency control - Jae Woong Shim (Wiley, 2021)
Abstract This paper proposes a vehicle‐to‐grid (V2G) operation methodology of electric vehicles (EVs) for frequency regulation, EV charging, and state‐of‐charge (SOC) management. This V2G operation methodology exhibits multifunctionality in regard to instantaneous power adjustment of EVs for primary frequency control during charging. The proposed method can stabilize grid frequency under the high penetration of renewable energy by simultaneously managing the desired state‐of‐charge (SOC) of the batteries. The results indicate that both charging and charged EVs can assist in frequency regulation so that V2G services can help embracing renewable energy sources and stabilize a power system. The feasibility of this method is verified by a practical power grid model to demonstrate the efficacy of EV charging control for SOC management using DIgSILENT/PowerFactory.